2006
DOI: 10.1099/jmm.0.46212-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacteria in endodontic infections by sequence analysis of 16S rDNA clone libraries

Abstract: A significant proportion of oral bacteria are unable to undergo cultivation by existing techniques. In this regard, the microbiota from root canals still requires complementary characterization. The present study aimed at the identification of bacteria by sequence analysis of 16S rDNA clone libraries from seven endodontically infected teeth. Samples were collected from the root canals, subjected to the PCR with universal 16S rDNA primers, cloned and partially sequenced. Clones were clustered into groups of clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
2
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 51 publications
7
58
2
8
Order By: Relevance
“…D. invisus was originally found in infected root canals of teeth with chronic apical periodontitis (20). Findings for this species are in line with findings from several other recent studies that demonstrated the presence of D. invisus in association with both asymptomatic and symptomatic endodontic infections (24,27,29,34). P. stomatis (or Peptostreptococcus sp.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…D. invisus was originally found in infected root canals of teeth with chronic apical periodontitis (20). Findings for this species are in line with findings from several other recent studies that demonstrated the presence of D. invisus in association with both asymptomatic and symptomatic endodontic infections (24,27,29,34). P. stomatis (or Peptostreptococcus sp.…”
Section: Discussionsupporting
confidence: 79%
“…P. stomatis (or Peptostreptococcus sp. clone CK035) is a newly named species that had been previously detected in infected canals only by studies using clone library analysis (29)(30)(31). This is the first study evaluating the occurrence of this species in a large number of root canal samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous molecular studies focused on the detection of selected Treponema species or phylotypes (4, 11, 13, 15, 25-27, 38, 40, 43, 46). Of the several studies that have performed broad-range analyses for overall bacteria in primary endodon- (41) 2 (6) 8 (11 (14, 22, 29, 31-33, 52, 53), only two reported the occurrence of spirochetes, and even those were a few species in a few cases (31,32). These studies using universal bacterial primers may underestimate spirochetal populations, especially if they are in low numbers in the environment (5,16).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to sampling, supragingival plaque was removed with sterile cotton pellets and the sites were isolated with cotton rolls to avoid saliva contamination. DNA was extracted as previously described by Saito et al (18). After DNA extraction, the presence of M. timidum was determined by a Nested Polymerase Chain Reaction (Nested PCR).…”
Section: Timidum Detectionmentioning
confidence: 99%